Minimum weight and maximum feasibility robustness approach for composite structures design - Carlos Alberto Conceição António (2019)
A robust design optimization (RDO) of composite structures addresses the design as a biobjective optimization problem with following objectives: (1) the weight of the structure which optimality is associated with performance robustness; and (2) the variability of structural response, which is associated with feasibility robustness of design constraints. Therefore, a bilevel dominance Multi-Objective Genetic Algorithm (MOGA-2D) solves the RDO of composite structures. The numerical tests show the capabilities of the approach.